ANALYSIS OF THE COMPLIANCE OF SELABINTANA TOURIST PARK MANAGEMENT WITH THE DSN-MUI FATWA ON SHARIA TOURISM - Rahayu, Sri; Mustofa, Mustofa; Nasrudin, Nasrudin; Jaenuddin, Jaenuddin; Hidayat, Agi Attaubah (Faculty of Islamic Economic and Business - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract: Selabintana Tourism Park has the potential to become a sharia-complient tourism destination as per DSN-MUI fatwa No.108/2016. Although it does not have binding legal force, this fatwa remains the main reference in the development of halal tourism in Indonesia. This study aims to analyze the implementation of the sharia tourism fatwa at Selabintana Tourism Park, Sukabumi Regency. The study uses a qualitative method with an empirical juridical approach. Data collection techniques were carried out through observation and interviews with tourism managers. The study reveals that Selabintana Tourism Park has implemented saveral principles of sharia tourism, including the provision of worship facilities, halal culinary products, environmental cleanliness, separate of sanitation facilities for men and women, and efforts to avoid activities that conflict with sharia. However, implementation has not been fully optimized due to the limited understanding of managers and the community regarding the concept of halal tourism, the absence of regional policies supporting halal tourism certification, and the lack of integration of sharia values into the destination management system. Collaboration with the Halal Product Guarantee Agency (BPJPH) is necessary to strengthen education, collaboration, and branding strategies in realizing sharia tourism. Keywords: fatwa of the indonesian ulema council (mui), sharia tourism, selabintana tourist park Abstrak: Taman Wisata Selabintana berpotensi menjadi pariwisata syariah yang berpedoman pada fatwa DSN-MUI No.108/2016, meskipun tidak memiliki kekuatan hukum yang mengikat, fatwa ini tetap menjadi referensi utama dalam pengembangan wisata halal di Indonesia. Penelitian ini bertujuan untuk menganalisis implementasi fatwa pariwisata syariah di Taman Wisata Selabintana, Kabupaten Sukabumi. Penelitian menggunakan metode kualitatif dengan pendekatan yuridis empiris. Teknik pengumpulan data dilakukan dengan observasi dan wawancara terhadap pengelola wisata. Penelitian menunjukkan bahwa Taman Wisata Selabintana telah menerapkan sebagian prinsip pariwisata syariah, antara lain penyediaan fasilitas ibadah, kehalalan produk kuliner, kebersihan lingkungan, pemisahan fasilitas sanitasi antara laki-laki dan perempuan, serta upaya menghindari aktivitas yang bertentangan dengan syariah. Namun, implementasi belum sepenuhnya optimal karena keterbatasan pemahaman pengelola dan masyarakat mengenai konsep wisata halal, belum adanya kebijakan daerah yang mendukung sertifikasi wisata halal, serta belum terintegrasinya nilai-nilai syariah ke dalam sistem manajemen destinasi. Kolaborasi dengan Badan Peneyelenggara Jaminan Produk Halal(BPJPH) diperlukan untuk penguatan edukasi, kolaborasi serta strategi branding untuk mewujudkan pariwisata syariah. Kata Kunci: fatwa dsn-mui, pariwisata syariah, taman wisata selabintana